Applying value stream management to improve production processes in LED manufacturing industry - a case study - Nguyen Nhu, Phong; Doan, Thuy Vy; Nguyen Nhu, Tu Anh (BOHR International Journal of Advances in Management Research, 2025)
The company under study is a company specializing in producing light-emitting diodes (LED). The revenue of the company has declined sharply in recent years. After analyzing, the root causes of the problem are high production lead time (LT) and high cycle time (CT) in the production process. The paper applied value stream management to improve the LED production process of the company. The primary objectives were to reduce the production LT and reduce the production CT to meet the takt time (TT) and therefore improve the revenue of the company. The results had shown that the LT had been reduced by 16.44%, from 235.5 minutes to 197 minutes, and the CT reduced by 36.68%, from 45.8 seconds to 29 seconds, meeting the TT